Surface of a tapered implant: Permukaan internal implan yang meruncing - Fitri Endang; Eri Hendra Jubhari (Makassar Dental Journal, 2022)
The choice of implant shape and size is an important part of the treatment plan procedure in order to obtain an implant that is sta-ble in masticatory function and aesthetic function. The use of implants with a tapered design and surface modification would improve the ultimate stability in low density bone. A comprehensiveand accurate radiographic examination is also an import-ant aspect of dental implant treatment planning. This article is aimed to present things about taperedinternal implants starting from indications, shape and dimensions, design, surface characteristics of the implant and drilling guide and selection of the appropriate type and radiographic technique to produce appropriate diagnostic information. So, with the limited facilities of modern radiographic images inIndonesia, conventional radiographic examinations with several projections can be used as an option to obtain optimal diagnostic information according to existing cases. Keywords: tapered implant, dental implant, dental implant radiography.